Analisis Implementasi E – Bupot Unifikasi terhadap Kepatuhan Pajak dalam Pelaksanaan Pengisian dan Pelaporan Pajak penghasilan Pasal 23 di PT HD Surabaya - Niken Fitriani; Muslimin Muslimin (AKUNTANSI 45, 2024)
This research aims to explore the effect of implementing E-Bupot Unification on tax compliance at PT HD Surabaya in withholding and reporting PPh 23. The descriptive qualitative method is the method used in this research. Data is collected from documents such as tax invoices, invoices, tax deposit letters, and other supporting documents. The research results show that PT HD has implemented E-Bupot Unification thoroughly and complies with applicable tax regulations, PT HD is compliant in fulfilling its obligation to deposit and report PPh Article 23 promptly. Apart from that, implementing the Unification E-Bupot at PT HD can facilitate withholding taxes, recording proof of withholding, creating e-billing, preparing master SPTs, and reporting Periodic SPTs. The findings of this research provide several practical implications, namely that the implementation of E-Bupot Unification can help increase tax compliance related to PPh Article 23.